Predicting Economic Development Through the PMJDY Index for Financial Inclusion : Evidence from India - Kaur, Ravinder; Singh, Ajay Pal; Mishra, Suyash (Indian Journal of Research in Capital Markets, 2025)
Purpose : This research aimed to examine the substantial influence of Pradhan Mantri Jan Dhan Yojana (PMJDY) on expanding financial access and driving economic progress. This was one such impactful initiative spearheading this crucial endeavor by providing financial services to the poor. Methodology : The PMJDY index for financial inclusion (PIFI) was developed in this study to assess financial inclusion by using three dimensions, i.e., â€œper capita saving account,â€ â€œper capita deposits,â€ and â€œper capita number of RuPay debit cardsâ€ delivered to PMJDY beneficiaries of Indian states and UTs. Economic growth was measured using GDP as a stand-in indicator, and linear regression analysis was used to test the hypothesis. Findings : The study supported the effective performance of banks in implementing PMJDY for financial inclusion and found a significant positive impact of financial inclusion through PMJDY on the Indian economy. Practical Implications : The results indicated that the government may improve financial inclusion by emphasizing additional financial inclusion elements related to PMJDY, such as growing bank branches, ATM networks, and loans. Originality : Unlike prior investigations on financial inclusion, this work framed an index to assess the PMJDYâ€™s influence on financial inclusion and overall economic growth.